PERANAN BIOCHAR SEBAGAI PEMBENAH TANAH PADA PERTANAMAN JAGUNG DI TANAH LEMPUNG BERPASIR (SANDY LOAM) SEMIARID TROPIS LOMBOK UTARA - Sukartono Sukartono; W.H. Utomo (BUANA SAINS, 2012)
The aims of this study to were evaluate potential of biochar for improving several soil physical characteristics and yield of maize in a sandy loam soil of North Lombok during three cyles of sowing times (December 2010-October 2011). Five treatments, i.e. application of coconut sheld biochar (BTK), application of cow dung biochar (BKS), application of famyard manure only for one season (PKA), applications of farmyard manure each season (PKB) and control (K). Biochar application increased C-organic, and concentration of nutrient (N, P, K, Ca and Mg), absorption of N, P, K and seed yield. During three seasons, application of biochar led to higher C-organic content and more stabile compared with farmyard manure application. It indicated that biochar was potential for sequenstration of CO2, increased micro pores and soil water retention. Water holding capacity of biochar treatment was higher than PKA (application farmyard manure only for one season) and control. Maize plants showed positive response to biochar applications. Seed yield of maize for three cyles of seasons were 5,54 t/ha, 5,51 t/ha for BTK and BKS, repectively. Application of manure each season, application of farmyard manure at one season and control treatments yielded 5,62, 5,36 and 4,83 t/ha of maize seed, respectively